A lattice Boltzmann model for heat transfer in heterogeneous media - Chen, Sheng; Yang, Bo; Zheng, Chuguang (Elsevier, 2016)
So far the lattice Boltzmann (LB) method has matured as a powerful tool to address a diversity of heat and mass transfer challenges. For most practical applications, the variation of thermophysical properties of working media will influence the performance of industrial systems substantially. However, nowadays the efforts to improve the LB method to consider variable thermophysical properties of working media are quite sparse. In the present work we firstly analyze the shortcomings of the available LB approaches for modeling working fluid with variable thermophysical properties. Based on the analysis, a simple LB model is proposed to overcome these shortcomings. The feasibility and reliability of the new LB model have been validated by three simple but nontrivial benchmark tests. Although it is originally proposed to simulate fluid flow with variable thermophysical properties, the present model can be extended directly to some other research areas where variation of thermophysical properties of working media should be considered, such as conjugate heat transfer between solid materials.